4 - L’exploitation des ressources uraniferes namibiannes et la politique nucléaire de l' Afrique du sud - Smail KHENNAS, (Africa Development, 1986)
Because of its colonial nature and its function as relay of impe rialism, the strategy of South Africa aims at perpetuating the rela tions of military and economic domination of Africa. Since the end of 1940's, the nuclear development of this country has also been ba sed on this principle. In this paper, the author argues that this polic is oriented more specifically to plundering the uranium resources of Namibia and building a military-civilian oriented nuclear industry. The transnational, public and private capital originating mostly from Britain, the United States, West Germany and France contributed in a significant way to the creation of the South African nuclear power The multiform aid (technological, industrial and financial) covering the major sections of the nuclear chain made it possible for South Africa to equip itself with a nuclear tool in which the civilian and military aspects are closely imbricated